Karakteristik Mutu Pancake Amerika Berbahan Dasar Mocaf dengan Penggunaan Proporsi Gula Pasir dan Baking Powder - Subarna Subarna; Muhammad Irfan Hakim; Tjahja Muhandri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2018)
Modified Cassava Flour (Mocaf) is a cassava (Manihot esculenta Crantz) flour commodity that have been modified fermentically with the usage of lactic acid bacteria. The purposes of this research are to formulate ingredients and to study the effect of the formulation toward physical and organoleptic cha-racteristics of the pancake made by mocaf. A Completely Randomized Design with the proportion of sugar (20, 30, and 40% based on Mocaf flour) and baking powder (2, 3, and 4% based on Mocaf flour) were used as treatment level. Mocaf pancake that was made with 20% sugar and 4% baking powder has the best physical, and organoleptic compared to the other treatments.